More than Meets the Eye: Age Differences in the Capture and Suppression of Oculomotor Action - Ridderinkhof, K. Richard; Wijnen, Jasper G. (Frontiers in Psychology, 2011)
Salient visual stimuli capture attention and trigger an eye-movement towards its location reflexively, regardless of an observer’s intentions. Here we investigate the effect of aging 1) on the extent to which salient yet task-irrelevant stimuli capture saccades, and 2) on the ability to selectively suppress such oculomotor responses. Young and older adults were asked to direct their eyes to a target appearing in a stimulus array. Analysis of overall performance shows that saccades to the target object were disrupted by the appearance of a task-irrelevant abrupt-onset distractor when the location of this distractor did not coincide with that of the target object. Conditional Capture Function analyses revealed that, compared to young adults, older adults were more susceptible to oculomotor capture, and exhibited deficient selective suppression of the responses captured by task-irrelevant distractors. These effects were uncorrelated, suggesting two independent sources off age-related decline. The fact that these process-specific age effects remained concealed in overall oculomotor performance analyses emphasizes the utility of looking beyond the surface; indeed, there may be more than meets the eye.